Structural strength analysis of unmanned aerial vehicle (UAV) wings with varying wingtip extension configurations - Pandie, Andry Renaldy; Azhary, Taufik; Kirillov, Aleksey Vladimirovich (Indonesian Journal of Aerospace, 2025)
This study investigates the structural performance of three wingtip configurations—single winglet, double winglet, and fence wingtip extension—for UAVs under specified static loading conditions using Patran/Nastran simulations. The analysis focuses on stress distribution and safety margins. The single winglet exhibits maximum stress, highlighting its capacity to safely withstand the applied loads while offering a simple design for easier manufacturing. The double winglet demonstrates reduced maximum stress, reflecting a balanced trade-off between strength and design complexity. The fence wingtip extension achieves the highest structural robustness, showcasing superior load-bearing capacity but with increased manufacturing complexity. The findings reveal that the fence wingtip extension is the most reliable in terms of structural strength and safety, making it suitable for high-performance UAV applications. Meanwhile, the single winglet emerges as the most practical option for cost-efficient production without compromising structural integrity. The double winglet is a viable compromise, combining moderate structural advantages with reasonable manufacturability.